ANALISIS JARINGAN KOMUNIKASI PADA KOMENTAR DEBAT PERTAMA CAPRES 2024 DI KANAL YOUTUBE KOMISI PEMILIHAN UMUM (KPU) - Sena Reselina; Sri Wahyuning Astuti (Program Studi Ilmu Komunikasi, 2024)
As the 2024 elections approach, political discussions and debates in Indonesia are heating up. These discussions also occur on social media platforms, particularly YouTube, which rapidly disseminates information, allowing a broad audience to access and engage with the content. This research aims to analyze the relationships among actors (nodes) and social networks in the comments on the first presidential debate of 2024 on the Komisi Pemilihan Umum (KPU) YouTube channel. Utilizing Social Network Analysis (SNA), this study identifies communication patterns, relationship types, and network connections formed from actor interactions. The findings reveal that the social network structure is a one-mode network with 6000 comments filtered to 2400 for analysis. The relationship types indicate key actors with high centrality, playing crucial roles in shaping public opinion and discussion dynamics. The communication patterns reflect significant issues discussed in the debate, influencing public responses to the presidential candidates' arguments. These insights offer a deeper understanding of social interaction dynamics on social media during political campaign periods. Keywords: Elections; Social Networks; YouTube; Actor Centrality; Presidential Debate